2021
DOI: 10.1002/anie.202013172
|View full text |Cite
|
Sign up to set email alerts
|

A Bidentate Iodine(III)‐Based Halogen‐Bond Donor as a Powerful Organocatalyst**

Abstract: In contrast to iodine(I)-based halogen bond donors,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
137
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(142 citation statements)
references
References 85 publications
2
137
0
3
Order By: Relevance
“…Remarkably, only 5 mol% iodine could be used in nitromethane, indicating that lower catalyst loadings should also be feasible in some solvents. A moderate yield (38 %) was also observed for dichloromethane in contrast to previous reports in the literature [21] . While very Lewis‐basic solvents like DMF or DMSO are known to interact with iodine and deactivate it for further reactions, [29] apolar solvents like toluene or pentane are also unsuitable for the iodine‐catalyzed Diels‐Alder reaction of 1 a .…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…Remarkably, only 5 mol% iodine could be used in nitromethane, indicating that lower catalyst loadings should also be feasible in some solvents. A moderate yield (38 %) was also observed for dichloromethane in contrast to previous reports in the literature [21] . While very Lewis‐basic solvents like DMF or DMSO are known to interact with iodine and deactivate it for further reactions, [29] apolar solvents like toluene or pentane are also unsuitable for the iodine‐catalyzed Diels‐Alder reaction of 1 a .…”
Section: Resultsmentioning
confidence: 60%
“…Although a direct comparison with other halogen‐bond donors used in Diels‐Alder reactions is somewhat difficult due to the different reaction conditions, [3d,5a,20,21] our investigations clearly demonstrate that iodine is superior to most of them and can also compete with bidentate iodine( iii ) systems. Interestingly, molecular bromine, which can occasionally be used to replace iodine as a catalyst, [41] is inactive under the reaction conditions.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…[12] Huber et al reported a series of pioneering studies on the catalytic use of cyclic dibenzoiodo-lium salts in a Diels-Alder cycloaddition [13] and a Friedel-Crafts reaction. [14] A study on the directional and soft character of XB catalysts comparing to the classical Lewis acid catalysts demonstrated the cationic 2-iodoimidazolinium-salt-catalyzed homo-and cross- [4 + 2] cycloadditions of 2-alkenylindoles, in which 2alkenylindoles were electrophilically activated by forming CÀ I•••π halogen bonds. [15] The present study applies hypervalent cyclic dibenzoiodolium salts to cycloadditions of 2-alkenylindoles.…”
mentioning
confidence: 99%
“…Ausschnitt aus der Rçntgenstrukturanalyse des XB-Donors 1. [40] Das Triflat-Anion ist fehlgeordnet. Ellipsoide sind mit 50 % Wahrscheinlichkeit angegeben.…”
unclassified